Predisposing factors and outcome of hypernatremia in breastfed late preterm and term neonates - Ramesh, S; Suvetha, K (Indian Journal of Child Health, 2017)
Background: Inadequate breastfeeding results in hypernatremia in otherwise healthy neonates. Objective: This study finds out the predisposing factors and clinical outcome of hypernatremia in breastfed late preterm and term neonates. Materials and Methods: A descriptive study was conducted in a tertiary hospital with retrospective data from July 2013 to June 2016. Babies with serum sodium ? 150 mEq/L were identified. Breastfed babies with little or no formula feeds, gestational age ? 34 weeks, and birth weight ? 2000 g were included. Babies with congenital anomalies, sepsis, prior parenteral fluid therapy and renal or endocrine diseases causing fluid and electrolyte disturbances were excluded. Total weight loss > 10% or daily weight loss > 5% from the birth weight were considered as excess weight loss. Results: A total of 201 babies were studied. Hypernatremia was significantly more common in babies of primiparous mothers (p < 0.01). There was no difference in incidence between vaginal born and cesarean?born babies. Positive correlation was seen between age at presentation, percentage of weight loss (p = 0.001) and serum sodium (p = 0.01). Significantly more cases were seen in summer season (p < 0.01). Excess weight loss, jaundice, fever, and dehydration were the common symptoms. Complications observed were acute kidney injury, seizures, intracranial bleed, apnea, and bradycardia. Babies with complications mostly presented after 7 days of age, had > 25% weight loss and had serum sodium ? 170 mEq/L. There was no death. Three babies had neurodevelopmental problems on follow?up. Conclusion: Breastfed babies of primiparous mothers and born in summer are predisposed to hypernatremia. Babies presenting at a later age had severe weight loss, severe hypernatremia, and complications.